Research on the Role of the Digital Economy in Promoting Low-Carbon Sustainable Development in China’s Cities - Li, Siqi (Transactions on Economics, Business and Management Research, 2024)
Against the backdrop of globalization and industrialization, cities, as hubs of economic, cultural, and social activities, are increasingly facing issues of carbon emissions and energy consumption. To address climate change and achieve sustainable development goals, low-carbon urban development has become a global consensus. As an emerging economic form, the economy of digit, with its efficient, intelligent, and green characteristics, offers new solutions for urban development of low carbon. The digital economy is not merely an accumulation of technologies, but rather a key pathway to achieving low-carbon, sustainable urban development. Through the application of digital technologies, it is possible to optimize energy structures, promote industrial upgrading and transformation, enhance the level of intelligence in urban management, and foster the formation of green consumption and lifestyles. However, the digital economy is merely a means; the true goal is to realize the low-carbon sustainable development of cities. The application of digital technologies needs to be combined with the joint efforts of governments, businesses, and society to achieve the greatest impact. To this end, it is essential to focus on actual development situations, strengthen technological innovation and application, improve data security and privacy protection mechanisms, formulate targeted policy guidance and regulatory measures, and promote the deep integration of the digital economy with urban low-carbon development to meet the demands of sustainable urban growth.